The effects of light wavelengths and light intensties on the aggressive behaviour of African catfish Clarias gariepinus juveniles - Sallehudin, Muhammad Firdaus; Yusoff, Nor Amira; Tan, Nai Han; Saad, Shahbudin; Mukai, Yukinori (2016)
The survival and growth rates of African catfish Clarias gariepinus were reported to be affected by light conditions. One of the methods to understand the effects of light conditions on fish survival and growth rates is through analysing the aggressive behavior of the fish. The objective of the present study was to analyse the aggressive behaviours of African catfish juveniles under different light wavelengths and light intensities. For this purpose, the behaviour of African catfish juveniles (age: 34 days old) was observed under five light wavelengths (white, blue, green, yellow and red) and three light intensities (0.0014, 0.014, and 1.40 µmoles/m²/s). The results showed that the aggressive behaviour of the juveniles were significantly affected by light wavelengths and light intensities. Among five light wavelengths, the juveniles showed less aggressive behaviour under yellow light wavelength. Futhermore, the juveniles also showed less aggressive behaviour under 0.0014 µmoles/m²/s. Therefore, rearing of African catfish juveniles under yellow light wavelength with light intensity of 0.0014 µmoles/m²/s can be recommended